Managerial Ownership, Debt Policy, and Dividend Policy as Determinants of Financial Performance - Ronni Andri Wijaya (Dinasti International Journal of Digital Business Management, 2026)
Consumer goods manufacturing companies face a double challenge in maintaining business continuity and making profits amid macroeconomic conditions that are not yet fully stable post-pandemic. This study aims to examine the influence of Managerial Ownership, Debt Policy and Dividend Policy. The population in this study consists of 97 consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020-2024. Sampling in this study used a Purposive Sampling technique, resulting in a sample of 95 observations from 19 companies. The data collection technique used was collecting secondary data from financial reports and official IDX publications. The findings show that Debt Policy and Dividend Policy have a significant effect on Financial Performance but Managerial Ownership has no effect on financial performance